The Effect of Sputum Delivery Time on the Sensitivity of Culture and AFB Microscopy in the Diagnosis of Drug-Resistant TB - Rizkiyah, Risa; Dwiyanti, Ratih Dewi; Insana, Aima (Baiman Bauntung Batuah Center, 2025)
Drug-resistant tuberculosis (DR-TB) is a major challenge in TB control in Indonesia. Early detection using liquid and solid media cultures is crucial due to the limited sensitivity of Acid-Fast Bacilli (AFB) microscopic examination. In addition, the time of sputum specimen delivery can also affect bacterial viability. This study aims to determine the relationship between liquid and solid media culture results with AFB microscopic results in immediate and delayed sputum in patients with DR-TB. This is an observational analytical study with a cross-sectional design, involving 40 sputum samples from DR-TB patients examined at the South Kalimantan Provincial Health Laboratory from January to April 2025. Samples were grouped based on the time of sputum delivery (<7 days = immediate; ?7 days = delayed), and examined using AFB microscopic methods, Mycobacterium Growth Indicator Tube liquid culture, and Lowenstein-Jensen solid culture. Data analysis was performed using the Spearman correlation test. Of the 40 sputum samples examined, 2 (5%) were positive by AFB microscopy, 8 (20%) were positive by liquid culture (MGIT), and 6 (15%) were positive by solid culture (Lowenstein-Jensen). The results showed that in immediate sputum, Mycobacterium tuberculosis (MTB) was detected in 7 samples using liquid media and in 5 samples using solid media. In contrast, in delayed sputum, only one sample was positive in both media. Most samples with negative AFB microscopy still yielded MTB growth in culture, particularly in immediate sputum. There was no significant correlation between AFB and liquid culture results in immediate sputum (p=0.172), but there was a substantial correlation between AFB and solid culture (p=0.025). In delayed sputum, both liquid and solid cultures showed a significant correlation with AFB results (p=0.046). Liquid culture was proven to be more sensitive than AFB microscopic examination, especially for immediately examined sputum. MTB viability and accuracy of results decreased in late-delivered sputum, so optimal specimen delivery management is necessary to maintain diagnostic quality.